Effects of Mobile Text Advertising on Consumer Purchase Intention: A Moderated Mediation Analysis - Hongyan, Lin; Zhankui, Chen (Frontiers in Psychology, 2017)
Mobile shopping is increasing in prevalence and has become a necessary part of many people’s daily lives. However, one main channel for mobile shopping, mobile shopping applications (apps), has not been thoroughly investigated. This study focused on mobile text advertising delivered from mobile shopping apps using the intention to purchase as the dependent variable for testing its marketing effect. In the context of a promotion focus vs. a prevention focus, we used Higgins’ regulatory focus theory combined with Ajzen's TPB and Herzog’s U&G to analyze the mechanism by which consumers formulate an intention to purchase in a mobile advertising context. This empirical study surveyed 320 consumers who had made a purchase using a mobile shopping app in the previous month. The results showed that infotainment, irritation, and subjective norms were significantly associated with attitudes; in turn, attitudes mediated the impact of these three factors on the intention to purchase. Moreover, a high promotion focus not only strengthened the positive effect of infotainment on attitudes but also intensified the mediation effect of attitudes between infotainment and the intention to purchase. A high prevention focus also consolidated the negative effect of irritation on attitudes as well as reinforced the mediation effect of attitudes between irritation and the intention to purchase. Furthermore, attitudes, subjective norms, and perceived behavioral control collectively impacted the intention to purchase. These findings shed light on ways to customize goods information in mobile advertising and have strong theoretical and practical implications.